Real-world treatment patterns of PCSK9 inhibitors among patients with dyslipidemia in Germany, Spain, and the United Kingdom. (4th May 2019) - Tai, Ming-Hui; Shepherd, Jason; Bailey, Hollie; Williams, Nathan; Hatz, Maximilian; Campos Tapias, Ignasi; Catterick, David; Worth, Gavin
Abstract: Objective: Proprotein convertase subtilisin/kexin type 9 antibody inhibitors (PCSK9i) are approved as adjuncts to maximal tolerated statin therapy to lower low-density lipoprotein cholesterol (LDL-C). This study describes real-world use, characteristics of PCSK9i users and non-users, and factors influencing treatment choice. Methods: A physician and patient survey was conducted in Germany, Spain, and the UK from December 2016 to April 2017 through the Adelphi Dyslipidemia Disease Specific Program. Physicians reported patients' lipid-lowering therapy (LLT) history and characteristics. PCSK9i users were systematically over-sampled. Results were summarized using frequencies and proportions. Results: The study included 110, 123, and 117 physicians from Germany, Spain, and the UK, respectively, providing data on 3, 073 patients (mean age = 62 years; 60% male). Most patients (63–73%) had prior statin and/or ezetimibe use. Compared to patients receiving other LLT ( n = 2686), PCSK9i users (222 in Germany, 97 in Spain, 68 in the UK) were, on average, 5–7.5 years younger and had LDL-C at diagnosis averaging 23–53 mg/dl higher. Familial hypercholesterolemia (FH), coronary heart/artery disease, myocardial infarction, and acute coronary syndrome were more common among PCSK9i users than non-users. PCSK9i users were also more likely to use high-intensity statins in their current LLT regimen (64–89% vs 28–50%). Physicians commonly reported PCSK9i benefits on LDL-C and total cholesterol as reasons for initiating these agents, and PCSK9i users reported good knowledge of cardiovascular disease and treatment options. Conclusions: Results indicate that physicians are prescribing PCSK9i to patients with high cardiovascular risk in accordance with European guidelines and reimbursement requirements.